Systematic Literature Review: Media Articulate Storyline Pendekatan Etnomatematika Untuk Meningkatkan Kemampuan Pemecahan Masalah - Reni Dwi Astutik; Eko Andy Purnomo; Venissa Dian Mawarsari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to solve mathematical problems is a crucial skill in the educational process, yet various studies show that this ability remains low among most students in Indonesia. One available option is the use of interactive media, Articulate Storyline, with an ethnomathematics approach. This study aims to systematically review the results of studies discussing the effectiveness of this media in developing mathematical problem-solving skills. The method used is a Systematic Literature Review (SLR) with the PRISMA framework. Data were collected through Google Scholar with specific inclusion criteria, resulting in 30 relevant articles published in the 2020–2025 period. The results of the study indicate that the ethnomathematics-based Articulate Storyline is consistently able to help students through the stages of problem-solving, from understanding the problem, planning strategies, implementing solutions, to broadcasting results. In conclusion, the use of this media effectively supports efforts to improve students' mathematical problem-solving abilities and has the potential to become an important strategy in mathematics.